STUDY EVALUASI JARINGAN DRAINASE KELURAHAN LOA IPUH KECAMATAN TENGGARONG - API, HAN (KURVA S JURNAL MAHASISWA, 2018)
The purpose of this study is to analyze the capacity of the existing drainage channel on Jalan Pasundan Samarinda adequately or not by comparing the discharge available in the field with maximum rain discharge. The current condition of the drainage network on the Loa Ipuh Urban Road Section is one of the roads in Tenggarong City. The drainage channel needs to be re-evaluated. Based on these problems, this study needs to be identified as to the cause of the Loa Ipuh Village Road channel in Tenggarong Sub-District which is not functioning optimally so that the solution to the problem can be determined. In its implementation, field studies are needed regarding the existing channel dimensions, the furthest path length, concentration time, and current land use utilization. In analyzing secondary data, it is necessary to calculate the extent of watershed, test hypotheses, statistical parametric analysis, frequency analysis, test the goodness of fit, determine the rain plan, and analyze the intensity of the rain plan. Rain intensity analysis plans for return periods 2, 5, 10 and 25 years respectively. After checking, it was found that the available capacity was not sufficient to accommodate the maximum rainfall that occurred so that a drainage system was needed to be repaired. One solution that can be applied is to make new drainage.